PERGESERAN NILAI-NILAI KESETIAAN DI ERA APLIKASI KENCAN: STUDI ETNOGRAFI FENOMENA TINDER DI MASYARAKAT DESA SUMBERDANTI JEMBER - Rifqi Maulana; Tasya Dwi Safitri (LPPM STAI Muhammadiyah Probolinggo, 2026)
Tinder is one of the most popular online dating apps used by many people in Indonesia. Tinder opens up opportunities for broad, fast, and personal communication. In the context of rural communities, especially in Sumberdanti Village, Sukowono District, the use of this app by married couples is an interesting social phenomenon to study because it can influence the values ​​of loyalty, trust, and integrity in the household. The focus of this research is: 1) How is the use of the Tinder app by married couples in Sumberdanti Village, Sukowono District? 2) What is the view of Islamic law and Article 1 of Law Number 1 of 1974 regarding the use of the Tinder app by married couples and its impact on family harmony? This research uses a qualitative approach and empirical legal research methods, data collected through in-depth interviews with several informants. Data were obtained through observation, interviews, and documentation of informants. The results of the study indicate that although the use of Tinder in Sumberdanti Village is not yet widespread, there are already several married couples who use it secretly. This has negative impacts on household harmony, such as decreased communication. According to Islamic law and Article 1 of Law No. 1 of 1974.